Ultrasound‐guided placement of long peripheral cannula in children with cystic fibrosis - Giardina, Massimiliano; Barillà, David; Crimi, Claudia; Arone, Amelia; Benedetto, Filippo; Lucanto, Cristina; Natoli, Rossella; Messina, Roberto; David, Antonio; Noto, Alberto (Pediatric pulmonology, 2022)
Background The natural history of cystic fibrosis (CF) lung disease is a chronic deterioration of lung function with intermittent episodes of pulmonary infectious exacerbations (PExs). Reliable venous access is a milestone of effective management of such exacerbations, managed both in hospital and outpatient chronic therapy. The aim of our study was to analyze the feasibility of ultrasound‐guided positioning of long peripheral catheters (LPC) as reliable midterm venous access in children affected by CF. Methods In this single‐center prospective study, over a 60‐month period, we included paediatric CF subjects admitted with PExs and undergoing intravenous antibiotic treatment. LPCs were inserted in all participants by paediatric anaesthesiologists with ultrasound guide technique. Prospective data were collected assessing catheter positioning procedure and complications. Results A total of 122 LPC insertions were performed in 55 CF children. Participants had a median age of 6.75 years (interquatile range: 3.7−13.5) at the time of catheter insertion. Implantation was successful on the first attempt in 86% of cases; 2 (1%) major insertion‐related complications were reported. Eighty‐eight percent of catheters were electively removed at the end of antibiotic therapy without any complication. Seven percent of the catheters were removed electively for occlusion and 2% for local dislodgment. Conclusions The results of the present study suggest that ultrasound‐guided positioning of LPCs are safe alternative means of peripheral venous access in children with chronic diseases such as CF.